Mechanism‐Dependent Modulation of Ultrafast Interfacial Water Dynamics in Intrinsically Disordered Protein Complexes. Issue 14 (28th February 2019) - Chowdhury, Aritra; Kovalenko, Sergey A.; Aramburu, Iker Valle; Tan, Piau Siong; Ernsting, Nikolaus P.; Lemke, Edward A.
Abstract: The recognition of intrinsically disordered proteins (IDPs) is highly dependent on dynamics owing to the lack of structure. Here we studied the interplay between dynamics and molecular recognition in IDPs with a combination of time‐resolving tools on timescales ranging from femtoseconds to nanoseconds. We interrogated conformational dynamics and surface water dynamics and its attenuation upon partner binding using two IDPs, IBB and Nup153FG, both of central relevance to the nucleocytoplasmic transport machinery. These proteins bind the same nuclear transport receptor (Importinβ) with drastically different binding mechanisms, coupled folding–binding and fuzzy complex formation, respectively. Solvent fluctuations in the dynamic interface of the Nup153FG‐Importinβ fuzzy complex were largely unperturbed and slightly accelerated relative to the unbound state. In the IBB‐Importinβ complex, on the other hand, substantial relative slowdown of water dynamics was seen in a more rigid interface. These results show a correlation between interfacial water dynamics and the plasticity of IDP complexes, implicating functional relevance for such differential modulation in cellular processes, including nuclear transport. Abstract : The dance of water : Water dynamics at the interface of intrinsically disordered proteins was studied on the femto‐ to nanosecond timescale by using a combination of advanced site‐specific spectroscopic tools. The results offer new insight into the relationship between solvation dynamics and the binding mechanism of proteins of central relevance to nuclear transport.